Comments on “Negative capacitance effect in semiconductor devices” - Ma, Jianguo (2009)
Capacitors play a very important role in the modeling of semiconductor devices. Without a good understanding and accurate model for the capacitance characteristics, one cannot model devices very well. The conventional equivalent circuit models of devices, such as MOSFET’s, MESFET’s, HEMT’s, and so on, are constructed mainly by using capacitors and resistors together with a voltage-controlled current-source. For fitting the measured terminal behaviors of a device, negative capacitances are often used. In the above paper,1 the authors tried to interpret the negative capacitance (NC) phenomenon theoretically in physics. However, we find some points in the above